Active zone assembly and synaptic release. (25th October 2006) - Kittel, R.J.; Hallermann, S.; Thomsen, S.; Wichmann, C.; Sigrist, S.J.; Heckmann, M.
Abstract : Neurotransmitter release at chemical synapses occurs when synaptic vesicles fuse to the presynaptic membrane at a specialized site termed the active zone. The depolarization-induced fusion is highly dependent on calcium ions, and, correspondingly, the transmission characteristics of synapses are thought to be influenced by the spatial arrangement of voltage-gated calcium channels with respect to vesicle release sites. Here, we review the involvement of the Drosophila Bruchpilot (BRP) protein in active zone assembly, a process that is required for the clustering of presynaptic calcium channels to ensure efficient vesicle release.